Impact of Mobile Banking on Customer Satisfaction of Nepalese Commercial Banks (NUTA Journal, 2024)
The aim of this research is to explore how mobile banking affects customer satisfaction in Nepalese commercial. The study employed a descriptive and causal comparative research design. Key independent variables identified include convenience, security, and fees and charges, while customer satisfaction serves as the dependent variable. The analysis encompasses customers from all 20 commercial banks operating in five different major cities of Nepal as population. To achieve the study's objectives, judgmental sampling from a non-probability sampling method was applied, and purposive sampling was used to select participants for the questionnaires. A total of 125 customers were chosen as samples from 6 different commercial banks. Multiple linear model was applied to analyze the data. The study found that customers are highly satisfied with the mobile banking services provided by commercial banks in Nepal. Majority of customers responded positively to each independent variable.